A finite separating set for Daigle and Freudenburg's counterexample to Hilbert's fourteenth problem - Dufresne, E; Kohls, M (Taylor and Francis, 2011)
This article gives the first explicit example of a finite separating set in an invariant ring which is not finitely generated, namely, for Daigle and Freudenburg's 5-dimensional counterexample to Hilbert's Fourteenth Problem.